The Effect of Openings Type on Indoor Temperature of Naturally Ventilated Buildings in The Tropical Climate - MuhammadIqbal; Atthaillah; Ahmad Nayan; Lena Indriani (Journal of Applied Science and Engineering)
In tropical climates, the utilization of naturally ventilated buildings is proposed as a means of addressing energy efficiency and thermal comfort challenges. This is achieved by allowing airflow from the outdoors to the indoors through designated openings. Nevertheless, the impact of diverse types of openings, including inlets and outlets, on indoor temperature remains a topic of ongoing investigation. The objective of this study is to explore various window types, their ratios, and their impact on indoor temperature. Onsite measurements were conducted in a test room, encompassing variables such as inlet wind velocity, outdoor and indoor temperatures, and relative humidity. The openings were categorized into singlesided openings with various ratios and cross-ventilation type, with outlets open or closed. The result indicates that the temperature difference between the evaluated cases is insignificant. This finding suggests that indoor temperature is primarily influenced by outdoor temperature and outdoor relative humidity, with higher opening ratios correlating with increased inlet velocity and indoor temperature. In addition, cross-ventilation type is more robust than singlesided ventilation to maintain the indoor temperature daily.